2003
DOI: 10.1039/b304609p
|View full text |Cite
|
Sign up to set email alerts
|

An alternative to the use of δ-lactam urethanes in the “ring switch” approach to higher homologues of AMPA-type glutamate antagonists

Abstract: In an alternative strategy to the use of delta-lactam urethanes for the preparation of homologues of AMPA-type glutamate antagonists, we have used 5-exomethylene derivatives of pyroglutamate esters. The homochiral pyrazole amino acid derivatives 18 and 19 have been prepared in this way. Although this synthesis yields products with a glycine residue separated from a heterocyclic ring by two carbon atoms, the substitution of the heterocyclic ring is different from that in compounds prepared from delta-lactam ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Cyclic enaminones in which a ring N atom is conjugated through an exocyclic double bond to two different carbonyl groups have found application in the synthesis of alkaloids (Wick et al, 1971), antitubercular indolizinones (Dannhardt et al, 1987) and potential glutamate antagonists (Hitchcock et al, 2003), among others. We required the title compound, (I), a simple example of this type of enaminone, as a precursor in our ongoing programme aimed at the total synthesis of indolizidine alkaloids (Michael et al, 1999).…”
Section: Commentmentioning
confidence: 99%
“…Cyclic enaminones in which a ring N atom is conjugated through an exocyclic double bond to two different carbonyl groups have found application in the synthesis of alkaloids (Wick et al, 1971), antitubercular indolizinones (Dannhardt et al, 1987) and potential glutamate antagonists (Hitchcock et al, 2003), among others. We required the title compound, (I), a simple example of this type of enaminone, as a precursor in our ongoing programme aimed at the total synthesis of indolizidine alkaloids (Michael et al, 1999).…”
Section: Commentmentioning
confidence: 99%
“…These combined findings suggested that these 1,3-dielectrophilic compounds can be expected to react with hydrazine derivatives in a very regioselective fashion. …”
Section: Results and Discussionmentioning
confidence: 97%
“…Treatment of 33 with 3M HCl removed only the Boc protecting group, 23 affording the desired 32 in 85% yield. Treatment of 35 with 3M HCl 23 produced the desired 34 in 66% yield. Scheme 3.…”
Section: Syntheses Of the Cyclic Metabolite And Its Tert-butyl Ester ...mentioning
confidence: 99%
“…The capacity for the tert-butyl ester and ethyl ester prodrugs of the L-γ-methyleneglutamic acid amides (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and the cyclic metabolite and its tert-butyl ester and ethyl ester prodrugs (31 -35) to inhibit the growth of the three breast cancer cell lines MCF-7, SK-BR-3, and MDA-MB-231 and the non-malignant MCF-10A breast cell line was assessed after 72 h of treatment (Figure 8). The potencies of all compounds on MCF-7 or SK-BR-3 cell lines were markedly reduced compared to those of previously identified leads (5, 6, or 9; Figure 2), and none exhibited a significant increase in potency compared to positive controls or were equipotent to compounds 5, 6, or 9.…”
Section: Evaluation Of the Synthesized Prodrugs And Cyclic Metabolite...mentioning
confidence: 99%
See 1 more Smart Citation